EFEKTIVITAS TERAPI RELIGIUS: BERDZIKIR SEBAGAI TEKNIK DISTRAKSI DALAM MENGATASI MASALAH PERSEPSI SENSORI: HALUSINASI PENDENGARAN - Afdillah Achmad Yufi; Alfunnafi Fahrul Rizzal (PT. Hasba Edukasi Mandiri, 2026)
Background: Schizophrenia remains a significant global health burden, with auditory hallucinations being the most prevalent symptom. These symptoms impair social functioning and increase the risk of relapse, requiring effective distraction techniques. Objective: This study aimed to evaluate the effectiveness of implementing spiritual Dhikr (Islamic mindfulness) as a distraction technique combined with Standard Nursing Action Protocols (SPTK) to manage auditory hallucinations. Methods: A descriptive case study approach was utilized involving two clients in the Garuda Ward at Dr. Radjiman Wediodiningrat Psychiatric Hospital. The intervention integrated the Standard Nursing Action Protocol (SPTK 1-4) with Dhikr as a distraction technique, conducted over five consecutive days for 15–30 minutes per session. Results: Following the intervention, both subjects demonstrated a significant reduction in the frequency of hallucinatory episodes. Objective observations indicated improved emotional stability, increased social interaction, and a greater capacity for self-control using the